El hombre con su contradicción" : del desflorador avergonzado al "hombre color mujer (2009)
ABSTRACT: The basis of this article is the idea that “the masculine” has an internal contradiction. This is supported by some freudian references, and brought out by Jacques Lacan’s formulations, particularly in his sexuation theory and his innovations on the borromean knot. We wonder how these statements explain the internal contradiction of masculinity, and we look for a possible answer in Lacan’s assertion that there is a “woman-colored man”, whose context corresponds to his theory of the sinthome.